Telomere DNA recognition in Saccharomycotina yeast: potential lessons for the co-evolution of ssDNA and dsDNA-binding proteins and their target sites - Steinberg-Neifach, Olga; Lue, Neal F. (Frontiers in Genetics, 2015)
In principle, alterations in the telomere repeat sequence would be expected to disrupt the protective nucleoprotein complexes that confer stability to chromosome ends, and hence relatively rare events in evolution. Indeed, numerous organisms in diverse phyla share a canonical 6 bp telomere repeat unit (5’-TTAGGG-3’/5’-CCCTAA-3’), suggesting common descent from an ancestor that carries this particular repeat. All the more remarkable, then, are the extraordinarily divergent telomere sequences that populate the Saccharomycotina subphylum of budding yeast. These sequences are distinguished from the canonical telomere repeat in being long, occasionally degenerate, and frequently non-G/C-rich. Despite the divergent telomere repeat sequences, studies to date indicate that the same families of single-strand (ss) and double-strand (ds) telomere binding proteins (i.e., the Cdc13 and Rap1 families) are responsible for telomere protection in Saccharomycotina yeast. The recognition mechanisms of the protein family members therefore offer an informative paradigm for understanding the co-evolution of DNA-binding proteins and the cognate target sequences. Existing data suggest three potential, inter-related solutions to the DNA recognition problem: (i) duplication of the recognition protein and functional modification; (ii) combinatorial recognition of target site; and (iii) flexibility of the recognition surfaces of the DNA-binding proteins to adopt alternative conformations. Evidence in support of these solutions and the relevance of these solutions to other DNA-protein regulatory systems are discussed.